Стан церебрального венозного кровобігу у хворих в положенні для струмектомії - Грубнік, В. В.; Тарабрін, О. О.; Буднюк, О. О.; Парфентьєв, Р. С.; Басенко, І. Л. (Clinical Endocrinology and Endocrine Surgery, 2012)
The purpose of work was studying the influence of the position for thyroidectomy and L-lysini aescinatis on a cerebral venous blood circulation. The analysis of data has shown that the position for thyroidectomy embarrasses cerebral venous circulation outflow and the use of L-lysini aescinatis improves it. Frequency of the headaches in the early postoperation period decreased from 14,3% to 5,7%.